Bisphenol A Down-Regulates The mRNA Expression of Steroidogenic Genes and Induces Histopathological Changes in Testes Of Rats - H Marghani Basma; I Ateya Ahmed; M Saleh Rasha; A Halawa Amal; A Eltaysh Rasha; F Awadin Walaa; Y Elseady Youssef (Journal of Veterinary Healthcare, 2018)
Bisphenol A (BPA) is an endocrine disruptor with a weak estrogenic effect used in industry as a component of food cans. We aimed to study the toxic effects of BPA on mRNA expression of steroidogenic genes and testicular structure in mature male rats. Animals were divided into 3 groups: vehicle control rats as first group, while second group received 10 µg/kg BW and third group received BPA 15 µg/kg BW orally every alternate day for a period of 105 successive days. Serum testosterone level, mRNA expression of genes related to steroid synthesis, histopathological examination, spermatogenesis index and number of Leydig cells were evaluated in this study. Lower serum hormone levels were observed in both BPA-treated groups as compared to the control group. The gene expression patterns of steroidogenic acute regulatory protein (StAR), cytochrome P450 17a(CYP17a) and 3β-Hydroxysteroid dehydrogenase (3β-HSD) were significantly down-regulated in BPA-treated rats compared to control group. Meanwhile, the expression of aromatase (CYP19) and lutinizing hormone receptor (LHR) was significantly up-regulated. Histopathological lesions were observed in the testes and epididymis of BPA-treated rats. Spermatogenesis index and the number of Leydig cells were significantly decreased in BPA-treated groups compared with the control group. This study highlights negative effect of BPA on steroidogenic genes and testicular structure in male rats.
Keywords: Bisphenol A